Board diversity and corporate social responsibility in Jordan. Issue 2 (3rd October 2016) - Ibrahim, Abdul Hadi; Hanefah, Mustafa Mohd
Abstract : Purpose: This study aims to investigate the impact of board diversity characteristics, namely, independence, gender, age and nationality of directors on the level of corporate social responsibility (CSR) disclosures. Design/methodology/approach: Content analysis was used to determine CSR disclosure. This study used panel data analysis to investigate the influence of board diversity characteristics on CSR disclosures. Findings: Panel data analysis show that the level of CSR disclosure has increased over the period of study. Results also reveal a positive and significant association between the level of CSR disclosure and board diversity variables. Research limitations/implications: This study examined only companies listed on Amman Stock Exchange. Therefore, the generalisation of the results might be limited to the listed companies only. Practical implications: Findings are relevant to policymakers, professional organisations and practitioners in Jordan and in other Arab countries. Social implications: The role of women in the boardroom is important to ensure more CSR activities by the listed companies. Jordan being a Muslim country should take the initiative to introduce laws to increase the number of women to the board. Originality/value: This study offers significant contributions to existing CSR literature in Jordan and in other Arab countries by introducing female directors. Findings are important to policymakers. They should implement quotas for women in the boardroom, and adopting such a policy will increase the participation of women in the decision-making process of the companies and reduce gender bias.